Ethno-tourism in the County of Buenos Aires, Costa Rica. The Lessons Learned and the Challenges (Revista LIDER, 2020)
The article summarizes results of the research on inter-county routes with an ethno-tourism approach in the Brunca region of Costa Rica (funded by the UNDP Program and managed by theMinistry of Economy, Industry and Commerce of Costa Rica. The objective of this study is to present the lessons learned and the challenges of 11 ethnotourism projects located in the county of Buenos Aires. The results show that ethno-tourism businesses are a major source of employment, aiming to rescue the cultural heritage of the area. They need training in languages, visitor management, quality, marketing, solid and liquid waste management, and environmental interpretation